Position and definition of the genus Paegniodes Eaton, 1881 based on redescription on the type species Paegniodes cupulatus (Eaton, 1871) (Ephemeroptera: Heptageniidae). Issue 4 (2nd October 2018) - Ma, Zhen-Xing; Han, Na; Zhang, Wei; Zhou, Chang-Fa
Abstract: The genus Paegniodes Eaton, 1881 and its type species P. cupulatus (Eaton, 1871) have never been described in detail completely. In this article, all stages are described and photographed. Compared to other heptageniid genera, the adults of P. cupulatus have a more colourful body, smaller hindwings but larger titillators. The nymphs of this species have no setae or tubercles on the body and no emarginations on the head capsule. They have smaller lamellae of the first gills, a wider labrum with a median notch, mandibles without setae on outer margins, maxillae with a row of setae and scattered setae on the ventral surface, cerci with mesal setae, and a median filament with setae on both sides. Both imaginal and nymphal stages of the genus have unique characters, so the taxon Paegniodes is recognized at the rank of genus here. It appears closely related to Rhithrogena Eaton, 1881.